One-way energy insulation using time-space modulated structures. (1st September 2018) - Yi, Kaijun; Karkar, Sami; Collet, Manuel
Abstract: The one-way energy insulation using time-space modulated structures is theoretically studied in this paper. Specifically, the time-space modulated structure in our studies possesses a traveling wave-like modulation. An extended scattering matrix method is developed and verified by comparing to the finite element method. The wave transmission through finite time-space modulated structures is studied using the proposed method. Results show that within the whole stop bands of the two fundamental Bloch modes of time-space modulated structures, one-way wave transmission is achievable. This non-reciprocal phenomenon can be exploited to realize one-way energy isolation in equivalent infinite or semi-infinite systems, which can be found in practice. The one-way energy isolation fails in finite systems due to a frequency conversion phenomenon resulting from the reflection.